Cold forging of sintered iron-powder preforms - Sutradhar G.; Jha A.K.; Kumar S. (My University, 2025)
The paper reports on an investigation into various aspects of cold forging of iron-powder preforms which have been compacted and sintered from atomised iron powder. An upperbound solution is constructed for determining the die pressures developed during the cold forging of iron powder under axisymmetric and plane-strain condition. The results so obtained are discussed critically to illustrate the interaction of the various parameters involved and are presented graphically. © 1995.